ARTIFICIAL INTELLIGENCE IN CONSECUTIVE INTERPRETING: OPPORTUNITIES, CHALLENGES, AND IMPLICATIONS FOR INTERPRETER TRAINING - Kasimova Adiba (International Journal of Literature and Language Studies, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed language-related professions, particularly translation and interpreting. While considerable research has focused on machine translation and simultaneous interpreting technologies, the implications of AI for consecutive interpreting remain underexplored. This article investigates the role of AI in consecutive interpreting, examining its influence on interpreter training, terminology management, speech recognition, note-taking support, and performance evaluation. Employing a qualitative literature-based analytical approach, the study synthesizes current research from interpreting studies, educational technology, and artificial intelligence. The findings indicate that AI enhances interpreter preparation, training efficiency, and linguistic resource management. However, concerns regarding cognitive dependency, contextual inaccuracies, ethical issues, and diminished critical thinking persist. The study proposes a human-centered AI integration framework for interpreter education and argues that AI should be regarded as a complementary rather than a substitutive technology. The novelty of this research lies in its interdisciplinary examination of AI specifically within the context of consecutive interpreting and its conceptualization of AI literacy as a core competence for future interpreters.